Cardiorespiratory stability during echocardiography in preterm infants. Issue 1 (21st December 2004) - Groves, A M; Kuschel, C A; Knight, D B; Skinner, J R
Abstract : Blood pressure, heart rate, and oxygen saturation were monitored prospectively during 40 echocardiography recordings on 17 preterm infants (25–29 weeks; 510–1430 g), to examine whether echocardiography can be performed without disturbing cardiorespiratory status in preterm infants. There was no impact on absolute blood pressure. Heart rate increased by a mean of 4 beats per minute, and oxygen saturation decreased by a mean of 1% during echocardiography. While these changes reached statistical significance they are not of clinical significance as they remained well within ranges seen during control rest periods. All readings had greater minute-to-minute variability during echocardiography but differences were small and again remained within physiological ranges.